2021
DOI: 10.1101/2021.08.02.454700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of short- and long-term responses to environmental stimuli shape seasonal transcriptome dynamics

Abstract: Plants must respond to various environmental factors that change seasonally. In a previous study, seasonally oscillating genes were identified by a massive time-series transcriptome analysis in a wild population of Arabidopsis halleri ssp. gemmifera, a sister species of Arabidopsis thaliana. To analyze the function of these seasonally oscillating genes, we established an experimental system to mimic seasonal expression trends using A. thaliana. Arabidopsis thaliana plants were cultured under conditions that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(71 reference statements)
1
1
0
Order By: Relevance
“…This analysis indicated that in A. halleri roots the genes with the strongest significant variation (both positive and negative) among Cd stress and control are, in any case, associated with responses to chemical and generic stimuli. This agrees with the evidence that A. halleri can perceive and respond appropriately to different environmental stimuli, modulating and integrating multiple stimulus information [54] and giving a specific response to a peculiar heavy metal [55]. Specifically, Cd induces oxidative stress due to the impairment between photosynthetic and respiration activities [56], which has also been described in A. halleri [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This analysis indicated that in A. halleri roots the genes with the strongest significant variation (both positive and negative) among Cd stress and control are, in any case, associated with responses to chemical and generic stimuli. This agrees with the evidence that A. halleri can perceive and respond appropriately to different environmental stimuli, modulating and integrating multiple stimulus information [54] and giving a specific response to a peculiar heavy metal [55]. Specifically, Cd induces oxidative stress due to the impairment between photosynthetic and respiration activities [56], which has also been described in A. halleri [12].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, abnormal responses of plants to stress rely on the elimination of crucial players from the stress-related networks [65]. This is because plants respond to specific stresses by modulating complex interconnected pathways in which some genes play crucial roles both in generalized and specific responses to stress [54,55]. In this sense, after hub identification, we detected genes with a significant differential expression under Cd stress by DESeq2 package to confirm hub gene predictions [34,35].…”
Section: Discussionmentioning
confidence: 96%